Peran ulul albab dalam membangun kepribadian cerdas dan berakhlak mulia - ’ILLIYYIN, NURIL (Maliki Interdisciplinary Journal, 2026)
The concept of ulul albab in the Qur’an, referring to those with sharp intellects and profound hearts, serves as a crucial inspiration for shaping intelligent and noble-charactered personalities in the modern era of disruption. This article elucidates the role of ulul albab as exemplars who integrate akal fikih—critical and analytical thinking—with spiritual sensitivity and noble ethics to confront contemporary challenges such as moral degradation, intellectual crises, and social injustices amid globalization and digital revolution. Through a general analysis of Qur’anic principles, the discussion highlights key traits of ulul albab including profound contemplation (tafakkur) of divine signs in nature and life, steadfastness (istiqamah) in moral integrity, and consistent righteous deeds (amal shaleh) in social justice and environmental care. These traits foster holistic character: not merely cognitively intelligent, but also wise, emotionally resilient, and socially responsible. This approach is highly relevant to contemporary Islamic education, particularly in Indonesia, where integration with Pancasila can enrich the formation of resilient generations via curricula emphasizing contemplation, character building, and sustainable action projects. The article concludes that adopting ulul albab values offers an effective strategy for self-development, educational reform, and visionary leadership training, producing change agents who harmonize intellect, heart, and action.